Parental knowledge and substance use among african american adolescents: influence of gender and grade level - Tebes, Jacob Kraemer; Cook, Emily C.; Vanderploeg, Jeffrey J.; Feinn, Richard; Chinman, Matthew J.; Shepard, Jane K.; Brabham, Tamika; Connell, Christian M. (Journal of Child and Family Studies, 2011)
Parental knowledge is defined as parental awareness and information about a child's activities, whereabouts, and associations that is obtained through parental monitoring, parental solicitation, or self-disclosure. Increased parental knowledge is generally associated with lower adolescent substance use; however, the influence of various contextual factors, such as adolescent gender and grade level is not well understood, particularly for different racial or ethnic groups. In the present study, we used Hierarchical Generalized Linear Modeling analyses to examine the longitudinal relationship of parental knowledge to adolescent substance use in the context of adolescent gender and grade level among 207 urban African American adolescents in grades 6-11. Results indicated that increased parental knowledge is associated with a concurrent lower likelihood of substance use across all types of substances examined (alcohol, tobacco, marijuana, other drug use, and any drug use), but it did not predict changes in substance use 1 year later for the entire sample. However, analyses by gender and grade level showed that for boys and middle school youth, parental knowledge was a protective factor for increases in substance use across 1 year. Findings are discussed in terms of their implications for prevention and health promotion interventions for adolescent substance use among African American youth.
Keywords: African American adolescents; Developmental differences; Gender; Parental knowledge; Substance use; dept.mat

Role of an Intermediary Organization and State Government Partnership to Advance Practice and Policy in Children’s Behavioral Health - Lang, Jason; Randall, Kellie; Kelly, A.; Bracey, Jeana; Bridges-Hightower, Jenny; Newkirk, Katie; Lu, Jack; Gregory, Francis; Duran, Tracy; Geib, Catherine; Bozak, Stephanie; Mackey, Jocelyn; et al. (Prevention Science, 2026)
Keywords: Behavioral health; Bridge (graph theory); Diversity (politics); General partnership; Government (linguistics); Intermediary organization; Partnership; Plan (archaeology); Policy; Public policy; Research; State (computer science); System development; Workforce; Workforce development; dept.psy